The influence of rainfall patterns on factor of safety for clayey soil slopes - Mohammad, Ashrafullah Shafi; Satyanaga, Alfrendo; Abilev, Zheniskan; Bello, Nura; Nadezhda, Kozyukova; Zhai, Qian; Moon, Sung-Woo; Kim, Jong (Frontiers in Built Environment, 2024)
The persistent trend of rising temperatures and shifting weather patterns caused by climate change has prompted significant concern around the world. This research aims to evaluate the instability of slopes in Almaty, Kazakhstan, under various rainfall patterns, groundwater tables, and slope geometries by incorporating the principles of unsaturated soil mechanics. However, there have been a limited number of studies incorporating the principle of unsaturated soil mechanics with constant rainfall patterns in Central Asia, particularly in Kazakhstan, on the impact of rainfall-causing landslides. Hence, in this research, GeoStudio software (SEEP/W and SLOPE/W) was used to simulate the factor of safety (FoS) and pore water pressure for the investigated slopes under different rainfall patterns. Results from Hyprop and statistical method show that the saturated volumetric water content is 0.502, whereas the residual one is 0.147 and for the permeability function the conductivity coefficient started to sharply decrease at the suction value of 2 kPa when the air-entry value was 24 kPa. Findings from numerical analysis show the change in FoS for the slope of 10 m height and 27-degree slope angle was 6%, 7%, 7%, and 8% for cyclic, delayed, advanced, and normal distributions, respectively. For the slope with 20 m height and the same 27-degree angle, the change in FoS was 8%, 10%, 8%, and 11% for the cyclic, delayed, advanced, and normal distributions, respectively. These same patterns were shown in slopes with 35-degree and 45-degree angles, having the same 10 m and 20 m heights. Comparatively, this shows that slopes under cyclic rainfall patterns (240 mm of rain within 12 days) are less prone to failure compared to slopes under continuous, delayed, or regularly distributed rainfall patterns. Moreover, an increase in slope height and angle also affect the FoS negatively. It should be noted that the results obtained are only applicable to clayey-loam soil.